Methodology for Developing Students’ Knowledge of Pharmacokinetics in Higher Medical Education - Odiljonova Aziza Baxtiyor qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Mastering the mathematical and biophysical principles governing drug absorption, distribution, metabolism, and excretion presents a profound cognitive challenge for undergraduate medical students. The transition from theoretical pharmacological memorization to dynamic, patient-specific dosage calculation requires specialized pedagogical frameworks that traditional didactic lectures consistently fail to provide. This investigation systematically evaluates the integration of a multimodal, active-learning curriculum—combining Case-Based Learning, the flipped classroom model, and in silico pharmacokinetic simulations—on the clinical competency of third-year medical students. Operating through a prospective, randomized educational trial, 420 students were stratified into a standard didactic cohort (n = 210) and a multimodal intervention cohort (n = 210) over a 16-week academic semester. The primary outcomes measured included theoretical knowledge retention, applied dosage calculation proficiency, and clinical reasoning utilizing Objective Structured Clinical Examinations. The analytical data revealed a massive divergence in applied clinical skills. Students in the multimodal cohort achieved a mean score of 88.4 ± 4.2% in complex therapeutic drug monitoring scenarios, drastically outperforming the standard cohort's 54.6 ± 6.8% (p < 0.001). The ability to accurately adjust loading and maintenance doses for narrow-therapeutic-index drugs in simulated acute kidney injury patients improved by an absolute margin of 41% following the intervention. These quantitative metrics definitively prove that interactive, visually driven simulation algorithms dismantle the cognitive overload associated with pharmacokinetics. Replacing passive lecture formats with dynamic, scenario-based mathematical modeling is a fundamental requirement for equipping future physicians with the precise pharmacological reasoning necessary to prevent iatrogenic toxicity.